Pendidikan Agama Islam Masa Kekhalifahan Turki Usmani, Kekhalifahan Safawi, dan Kekhalifahan Mughal - Darmawan, Dedi (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2023)
This study analyzes the development of Islamic religious education in three main caliphs: Ottoman, Safavid, and Mughal Turks. Using the literature study method, this research examines primary and secondary sources related to the development of religious education in the context of each caliphate. During the Ottoman Empire, the Islamic religious education system developed rapidly through the establishment of madrasas that offered an inclusive curriculum. Under the Safavid Caliphate, educational institutions such as madrasas and universities were emphasized, with the integration of Shia religious teachings and general sciences. The Mughal Caliphate also made a significant contribution to Islamic religious education through the construction of mosques, madrasas and collaborations with prominent scholars. All three caliphs emphasize Islamic religious education within a framework of religious tolerance and inclusivity. This study concludes that although with different approaches, these three caliphs paid great attention to the development of Islamic religious education. In different time spans, these caliphs have made important contributions to the understanding of Islam and its application in society. This literature study provides valuable insight into how Islamic religious education developed in the context of the various caliphs.